PERAN PENDAPATAN ASLI DAERAH DALAM MENDORONG KEMANDIRIAN FISKAL MELALUI KONTRIBUSI, EFEKTIVITAS, DAN DESENTRALISASI DI KOTA JAMBI - Sirait, Juwita; Junaidi, Junaidi; Parmadi, Parmadi (STKIP Subang, 2026)
This study aims to analyze the contribution, effectiveness, and degree of fiscal decentralization of Local Own-Source Revenue (PAD) of Jambi City during the 2020–2024 period. The background of this study is based on the importance of PAD as an indicator of regional fiscal independence in the era of regional autonomy, where local governments are required to optimize their revenue sources independently. The research method used is a quantitative descriptive approach using secondary data obtained from the Directorate General of Fiscal Balance (DJPK). The analysis was conducted using contribution ratios, effectiveness ratios, and fiscal decentralization degree ratios. The results show that the contribution of PAD to the total regional revenue of Jambi City is still relatively low, ranging from 22% to 33%, indicating a high dependence on transfer funds from the central government. The effectiveness level of PAD shows fluctuating conditions, where in several years the realization has not optimally achieved the predetermined targets. In addition, the degree of fiscal decentralization in Jambi City remains in the low category, indicating that the level of regional financial independence is not yet optimal. Therefore, efforts are needed to optimize the management of PAD sources and to diversify regional revenue in order to enhance sustainable fiscal independence.